Empowering and disempowering students in student– supervisor relationships - Schulze, Salome (Koers, 2012)
In South Africa, the issue of empowerment or disempowerment in student–supervisor relationships has not been adequately addressed. Research for this article therefore aimed at determining how students are empowered or disempowered in their relationships with their supervisors. The conceptual framework for the research comprised social constructivism, critical pedagogy and theory on the empowerment of students. In the phenomenological case study, 15 master’s and doctoral students with 9 different supervisors from one college at the University of South Africa, and who had recently graduated, were purposefully selected for interviews. The findings of the study revealed that the students were not always empowered through sustained two-way communication in a supportive environment. In order to empower students, supervisory styles need to change from power-centred to facilitationcentred supervision. The study also showed that many supervisors found it difficult to adopt this style in a distance-education environment. The study is significant for generating a model that illustrates the interaction between various forces related to supervisory practices. Some recommendations for improvement were made.